2016
DOI: 10.1002/stc.1923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of measurement and simulation errors in structural system identification by observability techniques

Abstract: This is the peer reviewed version of the following article: [Lei, J., Lozano-Galant, J. A., Nogal, M., Xu, D., and Turmo, J. (2017) Analysis of measurement and simulation errors in structural system identification by observability techniques. Struct. Control Health Monit., 24: . doi: 10.1002/stc.1923.], which has been published in final form at http://onlinelibrary.wiley.com/wol1/doi/10.1002/stc.1923/full. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
(46 reference statements)
5
27
0
Order By: Relevance
“…[35] Thus, the average is taken for those estimations falling into the range of [0.5, 1.5]. Table 1 presents the mean of the estimations of associated parameters under different error levels using eight measurements.…”
Section: Example 1 Without Compatibility Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Thus, the average is taken for those estimations falling into the range of [0.5, 1.5]. Table 1 presents the mean of the estimations of associated parameters under different error levels using eight measurements.…”
Section: Example 1 Without Compatibility Conditionsmentioning
confidence: 99%
“…The worse accuracy observed in b EI 3;r compared with those results of b EI 1;r and b EI 2;r are in accordance with a previous study. [35] In fact, for a given load test, the lowest the curvature in a given area of the structure, the worst the accuracy of the estimated parameters in that zone.…”
Section: Example 1 With Compatibility Conditions: Effect Of the Nummentioning
confidence: 99%
“…However, wide applications of inclinometers can be found in civil engineering practice, such as stadiums Design Plaza Building , high‐rise buildings, and bridges . In the study of the effect of measurement types on the estimation accuracy in a four‐node simply supported beam, it was found that the rotations were much less sensitive to errors than the vertical deflections . However, systematic investigation on the effect of including rotation measurements on the estimation accuracy in static SSI is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These essential sets can be found via SSI by constrained OM . In a previous study, the estimation accuracy using essential sets are not satisfactory when measurement error exists . Hence, redundant sets (essential sets plus redundant measurements) are used to reduce estimation errors.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of physics‐based models represent the structural characteristics, for example, elastic modulus, inertias, and mass, whereas the parameters of the nonparametric models are weight factors of the adopted basis functions, which have no physical meaning and are determined by minimizing the discrepancy between the predicted and the measured response. From a statistical perspective, SSI methods can be categorized as probabilistic methods or deterministic methods . In the probabilistic methods, structural parameters are treated as random variables and their distributions are specified using prior knowledge.…”
Section: Introductionmentioning
confidence: 99%